Cadernos de planejamento docente : um olhar para as práticas alfabetizadoras na educação infantil (2000-2013) - Aquino, Andréa Cristina Nassar de (2015)
This survey, conducted within the Literacy and Literacy School Research Group (ALFALE), aims to analyze fourteen books planning a literacy teacher, used between 2000 and 2013, in order to identify continuities and changes in initial pedagogical practices literacy. The investigation is located in a perspective of Cultural History since, to this perspective, common objects can also keep records or features of an era that become rich historical sources, and that the study of the past, from such sources, enables us to reflect about our own reality and the reality of the world around us. In the history of education, the search for these files is being increasingly used in recent decades. This approach to question and analyze the "how to" consolidated a fruitful area for research as culture and knowledge are built within schools, and also how people absorb and produce this crop. To support this work, the authors were used as Le Goff (1996) Chartier (2000), Mignot (2008), Gvirtz (1999), among others. The school notebooks are documentary sources that generate information about the daily school and the teaching-learning process. Although there are different models and usage, notebooks are important documents that are interwoven with the history of education, can bring the richness of a story filed between pages that reveal the pedagogical practices of the teacher over time. We conduct research for the reconstruction of this process with an analysis of their sources and the holding of oral testimony by the teacher. There was also a look at notebooks and loose sheets of his students in an attempt to provide greater enrichment of data sources.The analysis was based on the following categories: or) paratextuals elements; b) Organizational structure of the planning; c) storytelling and / or reading stories; d) Interdisciplinarity as a methodological option; e) reading and writing activities; f) Work with different genres. The results show, first, the importance researched sources, the contract planning, showing how these records, you can read various aspects of school culture and thus offering us the opportunity to meet some of the pedagogical practice the authors of these manuscripts. On the other hand, proved that there were changes in the way work the mother tongue, and the teacher investigated awarded each year, more importance to the literacy process, understood by her as ownership of the alphabetic writing system, through enhanced the amount of tasks and work in an interdisciplinary manner, thus promoting literacy. According to her, these results were obtained with the training of teachers in the course of his career. Some constants were observed, but the changes were in greater quantity, considering the categories we choose toanalyze.